APPLICATION OF NEUTRON METHODS COMPLEX FOR DETERMINATION OF PETROPHYSICAL PROPERTIES OF RESERVOIRS - BONDARENKO, M.; KULYK, V.; KARMAZENKO, V.; KASHUBA, G.; SNIZHKO, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
On the basis of the performed investigations a possibility to determine porosity, type of saturation and litology of reservoir with the help of the new complex multispacing tool for fit measuring of the count rate of slow and epithermal neutrons is presented.